Respite Care for Caregivers of Older Adults - Suzanna Smith (EDIS)
“My 90-year-old grandmother lived with my mom and dad in her final years. She was comfortable there and had the help, support and affection she needed. My parents prepared healthy meals for her, took her shopping, to doctor’s appointments, and to visit friends. My grandmother knew she was safe, secure, and loved.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, August 2012.